Epiphytic lichen diversity and sustainable forest management criteria and indicators: A multivariate and modelling approach in coppice forests of Italy. (August 2020) - Brunialti, Giorgio; Frati, Luisa; Calderisi, Marco; Giorgolo, Francesca; Bagella, Simonetta; Bertini, Giada; Chianucci, Francesco; Fratini, Roberto; Gottardini, Elena; Cutini, Andrea
Highlights: We tested lichens as sustainable forest management indicators in coppice forests. A multivariate statistical and modelling approach was used. Biodiversity, health and protective function of forests drive lichen diversity. Models found some suitable indicator species for long term studies in coppices. Abstract: Epiphytic lichens represent one of the most suitable indicators of forest continuity and management, especially in the context of ancient and old-growth forests. Nevertheless, they have not yet been included among Sustainable Forest Management (SFM) indicators to which Pan-European forest policy and governance refer. In addition, currently adopted SFM indicators are mainly designed for high forests rather than coppice forests, despite the fact that today this management system covers more than 10% of the total European forests. In this study we investigated these two issues by examining epiphytic lichen diversity in three coppice forest stands, located in the two Italian regions of Tuscany and Sardinia. In particular, we addressed: i) the role of lichen diversity as SFM indicator and ii) its relationship with consolidated and new SFM indicators dealing with structural, health, biodiversity, protective and socioeconomic functions. Multivariate Factor Analysis and Generalised Linear Models were adopted for data analysis. We found that lichen diversity and the frequency of single sensitive species were mainly related to the biodiversity of plants and fungi (Criterion 4), the health and vitality of the forests (Criterion 2) and their protective functions (Criterion 5). Furthermore, our results show that the lichen species highlighted by the models may represent suitable indicators in long-term studies, especially in relation to complex and interconnected aspects of sustainable forest management. Although our findings represent a first contribute to this issue, more in-depth researches will be needed to clarify further aspects of the complex interactions among SFM indicators in the context of coppice forests.